Indonesia's Post-Pandemic Economic Recovery Strategy Through a Digital Transformation Approach - Panca Wahyuningsih; Daniel Kartika Adhi; Nurrohmi Ambar Tasriastuti; Endang Kurniawati (Economics And Business Management Journal ( EBMJ ), 2025)
The COVID-19 pandemic has severely affected Indonesia’s economy, especially micro, small, and medium enterprises (MSMEs). This study aims to analyze Indonesia’s post-pandemic economic recovery strategy based on digital transformation. Employing a mixed methods approach, the research collected quantitative data from surveys of 150 MSMEs across three provinces and qualitative data from interviews and policy document analysis. Results reveal a significant positive correlation between digital technology adoption and MSME income growth. However, infrastructure challenges and low digital literacy remain major barriers. Strengthening the digital ecosystem through infrastructure development, digital literacy training, and cross-sector collaboration is critical to support sustainable economic recovery. The findings provide insights for policymakers to enhance MSME digitalization as a cornerstone of national economic recovery.